(untitled) (Economic studies journal, 2023)
This study aimed to identify the relationship between job security and burnout with its components (emotional exhaustion, dulled feeling, and personal achievement). This study used the descriptive and analytical approach and reached results, the most important of which is the existence of a statistically significant relationship between job security and burnout. Likewise, employees at the North African Bank suffer to a high degree from burnout with regard to both the dimensions of emotional stress and dullness of feeling. In light of these results, the researchers recommended recommendations are paying more attention to incentives, wages, and compensation, providing more opportunities for advancement and career development, and developing strategies that increase levels of job security, which would increase their stability at work.